2019
DOI: 10.1049/iet-map.2018.5778
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturised microstrip patch design based on highly capacitive defected ground structure with fractal boundary for X‐band microwave communications

Abstract: This article proposes a new class of miniaturised microstrip patch design for wireless communications at 10 GHz. Antenna miniaturisation is achieved here by loading a highly capacitive modified Minkowski fractal (type‐2) defected ground structure (MFDGS‐II) exactly beneath the center of the radiating patch. The proposed methodology involves sensitivity analysis to select best DGS configuration. The resonant frequency corresponding to the patch is reduced from 16.832 GHz to 10 GHz incorporating MFDGS‐II without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The antennas stated in [11, 15, 16, 20] have compact size but the bandwidth of those antennas is less than the proposed CSK fractal antenna. In [19], an antenna has four resonant frequencies, which is higher than the proposed antenna but the size is larger and gain is not reported.…”
Section: Measured Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antennas stated in [11, 15, 16, 20] have compact size but the bandwidth of those antennas is less than the proposed CSK fractal antenna. In [19], an antenna has four resonant frequencies, which is higher than the proposed antenna but the size is larger and gain is not reported.…”
Section: Measured Results and Discussionmentioning
confidence: 99%
“…In recent days, several antennas are developed based on the fractalizing techniques which include Koch snowflake fractal [9], Sierpinski fractal [10][11][12], periwinkle flower-shaped fractal [13], "X" shaped fractal [14], Minkowski curve [15,16], and spidron fractal [17] for various wireless applications. However, to the best of the authors' knowledge, a limited number of antennas is reported by the researcher for emergency management.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal structures are preferred because of their main properties such as selfcorrelated, space-lling, and fractional ratios. Thus, fractal antennas are more bene cial over conventional microstrip patch antennas because they provide multiband/broadband behavior along with size miniaturization [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the literature survey prepared in this concern; it is perceived that there are many shapes of fractal structures that are used in antenna designs such as Koch snow ake, Sierpinski carpet, Sierpinski gasket, Minkowski fractals, Moore, and Hilbert curve along with some different shapes over a period of time [7][8][9][10][11][12][13]. In addition, various researchers have presented some ideas related to cross, plusshape, and Chaucer shape fractal antennas due to their simple geometries.…”
Section: Introductionmentioning
confidence: 99%
“…These areas comprise, among others, wireless communications [1] (including 5G technology [2]), internet of things (IoT) [3], [4], wearable [5] or tele-medicine appliances [6]. Design of antennas for these applications requires maintaining small physical dimensions [7], [8], which makes the task even more challenging. From the utility perspective, contemporary antenna structures have to fulfill various demands, including multi-band or MIMO operation [9], [10], polarization/pattern diversity [11], [12] or harmonic suppression [13].…”
Section: Introductionmentioning
confidence: 99%